Indirect Treatment Comparison of Talimogene Laherparepvec Compared with Ipilimumab and Vemurafenib for the Treatment of Patients with Metastatic Melanoma. Issue 4 (April 2016) - Quinn, Casey; Ma, Qiufei; Kudlac, Amber; Palmer, Stephen; Barber, Beth; Zhao, Zhongyun
Abstract Introduction Few randomized controlled trials have compared new treatments for metastatic melanoma. We sought to examine the relative treatment effect of talimogene laherparepvec compared with ipilimumab and vemurafenib. Methods A systematic literature review of treatments for metastatic melanoma was undertaken but a valid network of evidence could not be established because of a lack of comparative data or studies with sufficient common comparators. A conventional adjusted indirect treatment comparison via network meta-analysis was, therefore, not feasible. Instead, a meta-analysis of absolute efficacy was undertaken, adjusting overall survival (OS) data for differences in prognostic factors between studies using a published algorithm. Results Four trials were included in the final indirect treatment comparison: two of ipilimumab, one of vemurafenib, and one of talimogene laherparepvec. Median OS for ipilimumab and vemurafenib increased significantly when adjustment was applied, demonstrating that variation in disease and patient characteristics was biasing OS estimates; adjusting for this made the survival data more comparable. For both ipilimumab and vemurafenib, the adjustments improved Kaplan–Meier OS curves; the observed talimogene laherparepvec OS curve remained above the adjusted OS curves for ipilimumab and vemurafenib, showing that long-term survival could differ from the observed medians. Conclusion Even with limited data, talimogene laherparepvec, ipilimumab, and vemurafenib could be compared following adjustments, thereby providing a more reliable understanding of the relative effect of treatment on survival in a more comparable patient population. The results of this analysis suggest that OS with talimogene laherparepvec is at least as good as with ipilimumab and vemurafenib and improvement was more pronounced in patients with no bone, brain, lung or other visceral metastases. Funding Amgen Inc.